Draft Annual Plan 2003-2004 Government of Arunachal Pradesh - Planning Commission (Planning Commission, 2003)
Arunachal Pradesh, situated in the extreme North East of India, has an area of 83,743 sq. kilometers making it the largest state in the North- East. the population density is 13, hence the State is the most sparsely populated in the country. It has international borders on three sides: Bhutan on the west, China on the north and north-east and Myanmar on the east. the total length of international border is about 1630 kilometers. It has inter-state borders with Nagaland and Assam.
Government of Arunachal Pradesh, Department of Planning